2010
DOI: 10.1039/b921210h
|View full text |Cite
|
Sign up to set email alerts
|

Surface diffusion in porous catalysts

Abstract: This paper presents the application of pulsed field gradient (PFG) nuclear magnetic resonance (NMR) to observe surface diffusion of 1-octene in porous 1 wt% Pd/theta-Al(2)O(3) catalyst trilobes. We demonstrate for the first time the ability to identify diffusion on the pore surfaces unambiguously at ambient conditions in saturated porous media; this technique is applicable to microporous and mesoporous materials in general. At very short observation times, two distinct diffusion regimes are present. These are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
51
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(54 citation statements)
references
References 65 publications
1
51
2
Order By: Relevance
“…Over the past decades, it has emerged as an important concept in many areas of surface science, including catalysis, epitaxial growth, and electromigration of voids (3)(4)(5)(6)(7). Here, we demonstrated that surface diffusion also plays a pivotal role in determining the growth pathway of a seed and thus the shape or morphology taken by the final product in a solutionphase synthesis of metal nanocrystals.…”
mentioning
confidence: 82%
“…Over the past decades, it has emerged as an important concept in many areas of surface science, including catalysis, epitaxial growth, and electromigration of voids (3)(4)(5)(6)(7). Here, we demonstrated that surface diffusion also plays a pivotal role in determining the growth pathway of a seed and thus the shape or morphology taken by the final product in a solutionphase synthesis of metal nanocrystals.…”
mentioning
confidence: 82%
“…However, T 2 is further influenced by a translational correlation time associated with surface diffusion 27. 28 Consequently, when molecules adsorb on surfaces, changes in their translational and rotational dynamics influence T 2 more than T 1 , resulting in T 1 > T 2 29. In porous materials with a high surface‐to‐volume ratio, S / V , the observed relaxation rates are proportional to S / V ,30 so absolute T 1 and T 2 measurements cannot be readily used to compare interactions between materials with differing pore geometry, pore size and density of adsorption sites.…”
Section: Introductionmentioning
confidence: 99%
“…This effect is denoted as pore diffusion [69]. On the pore surface, the molecular dynamics is altered by liquid-surface interaction (adsorption) as well as limited diffusion path, which can be described as surface diffusion [70].…”
Section: Pore and Surface Diffusionmentioning
confidence: 99%